An escape theory model for directionally moving prey and an experimental test in juvenile Chinook salmon. Issue 8 (28th April 2020) - Sabal, Megan C.; Merz, Joseph E.; Alonzo, Suzanne H.; Palkovacs, Eric P.
Abstract: Prey evaluate risk and make decisions based on the balance between the costs of predation and those of engaging in antipredator behaviour. Economic escape theory has been valuable in understanding the responses of stationary prey under predation risk; however, current models are not applicable for directionally moving prey. Here we present an extension of existing escape theory that predicts how much predation risk is perceived by directionally moving prey. Perceived risk is measured by the extent antipredator behaviour causes a change in travel speed (the distance to a destination divided by the total time to reach that destination). Cryptic or cautious antipredator behaviour slows travel speed, while prey may also speed up to reduce predator–prey overlap. Next, we applied the sensitization hypothesis to our model, which predicts that prey with more predator experience should engage in more antipredator behaviour, which leads to a larger change in travel speed under predation risk. We then compared the qualitative predictions of our model to the results of a behavioural assay with juvenile Chinook salmon Oncorhynchus tshawytscha that varied in their past predator experience. We timed salmon swimming downstream through a mesh enclosure in the river with and without predator cues present to measure their reaction to a predator. Hatchery salmon had the least predator experience, followed by wild salmon captured upstream (wild‐upstream) and wild‐salmon captured downstream (wild‐downstream). Both wild salmon groups slowed down in response to predator cues, whereas hatchery salmon did not change travel speed. The magnitude of reaction to predator cues by salmon group followed the gradient of previous predator experience, supporting the sensitization hypothesis. Moving animals are conspicuous and vulnerable to predators. Here we provide a novel conceptual framework for understanding how directionally moving prey perceive risk and make antipredator decisions. Our study extends the scope of economic escape theory and improves general understanding of non‐lethal effects of predators on moving prey. Abstract : The authors present a new economic escape theory model applicable to directionally moving prey to understand how moving animals make antipredator decisions. Directionally moving animals are ubiquitous across ecosystems and these animals are especially vulnerable to predation. The authors framework illustrates how these animals assess risk and make antipredator decisions.